Survival, reproduction, and life history traits evaluation of heterocephalobellus sp. and cephalobus sp. from an artisanal and small-scale gold mine site, Davao de Oro, Philippines as bioindicators of heavy metal contamination - Mondejar, Alissa Jane S.; Paglinawan, Florifern; Tabelin, Carlito Baltazar; Aguilos, Maricar; Aguilos, Rustum; Opiso, Einstine M.; Martinez, Joey Genevieve T.; Metillo, Ephrime B.; Sumaya, Nanette Hope N.; Villacorte-Tabelin, Mylah (2023)
Mining is notorious for contaminating the environment with heavy metals, disrupting the activities of soil fauna such as nematodes, and causing changes in the functions of organisms in the soil ecosystem. This study investigated the survival, reproduction, and typical life history traits (LHTs) of free-living nematodes collected from an artisanal and small-scale gold mine (ASGM) site, including how heavy metals influenced these parameters. Morphological and molecular analyses identified Heterocephalobellus sp. and Cephalobus sp. (Rhabditida: Cephalobidae) from the soil, which were cultured in a bacteriological agar to assess their LHT using the hanging drop technique. These cultured nematodes were then exposed to different temperatures (20, 25, and 30 °C) to determine the optimum conditions for their survival and reproduction. Cultured nematodes were also exposed to copper (Cu), lead (Pb), and zinc (Zn) to elucidate the effects of these heavy metals on the nematode’s survival, reproduction, and LHT. Our results suggest that the ideal temperature for survival with a high reproduction rate for both species was at 25 °C. Exposure to heavy metals led to decreased survival and reproduction at 25 and 30 °C in both nematodes. In contrast, these nematodes survived longer at 20 °C with delayed reproductive maturity. At 25 °C, the LHT of Heterocephalobellus sp. showed a shorter population generation time with a decreased number of offspring. Although a shorter population generation time was also observed in Cephalobus sp., more offspring were produced when exposed to heavy metals. Altogether, these results suggest that when exposed to heavy metals, Heterocephalobellus sp. and Cephalobus sp. led to changes in their survival and reproduction. To the best of our knowledge, this is the first report evaluating the survival, reproduction, and LHTs of Heterocephalobellus sp. and Cephalobus sp. in the Philippines and how these parameters are affected by heavy metals ubiquitous in mine sites.
Keywords: Nematoda; Life cycle costing; Morphology; Heavy metal contamination; Mineral industries